AN ANALYSIS OF LIFE CYCLE SUSTAINABILITY ASSESSMENT ON THE SUGAR PRODUCTION PROCESS IN PT X - Dina, Atikah Aulia; Tama, Ishardita Pambudi; Gapsari, Femiana; Ayunin, Aliya Qurrota (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Among the industries that have detrimental effects on the environment is the sugarcane sector. Consequently, it is possible to draw the conclusion that the sugarcane sector is not environmentally sustainable. According to the study's findings, the primary cause of all damage categories is the usage of power produced through bagasse cogeneration. With a total score of 71,2%, human health makes the largest contribution to the harm categories. It is anticipated that this research's findings will lessen PT X's environmental effect, making the company more environmentally sustainable.